WORLD QURAN HOUR: USM CELEBRATES GLOBAL QURAN-READING EVENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 11 September 2016 The campus and surrounding community of Universiti Sains Malaysia (USM) participated in the simultaneous reading of the Quran in the World Quran Hour event here this morning.